1999
DOI: 10.1055/s-2007-971150
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Summer Camp Endurance Training on Non-Specific Immunity in Long-Distance Runners

Abstract: The present study was conducted to investigate the effects of endurance training during a 1-month summer camp on the non-specific host defence systems of ten highly trained male long-distance runners. Examinations with informed consent were carried out three times: 2 days before the training began, an intermediate day, and 2 days after the camp. The subjects ran a total of about 800 km during the camp. Neutrophilic reactive oxygen species (ROS) generation determined by luminol- and lucigenin-dependent chemilum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
2

Year Published

2006
2006
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 12 publications
0
15
2
Order By: Relevance
“…Furthermore, the changes in LgCL and LmCL in SOA are different from the results of Sato's and Kumae's reports (13,30) and similar to the results of Saito's and Mochizuki's reports (28,29). The reason for this might be due to the difference in the exercise load or the subjects' physical condition.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Furthermore, the changes in LgCL and LmCL in SOA are different from the results of Sato's and Kumae's reports (13,30) and similar to the results of Saito's and Mochizuki's reports (28,29). The reason for this might be due to the difference in the exercise load or the subjects' physical condition.…”
Section: Discussioncontrasting
confidence: 71%
“…Many studies have examined the relationship between neutrophil ROS production capability and exercise or short-and long-term training (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). However, only our studies have researched the changes in SOA following exercise or training (13,(28)(29)(30) and the results of these are summarized in Table 1. In general, this data has shown that exercise increases SOA.…”
mentioning
confidence: 99%
“…A control opsonized zymosan (OZ) was prepared using pooled human serum obtained from health adults. [5] The pooled human neutrophils (60 μL, 6.0 × 10 4 cells) isolated from the healthy adults were placed in each well of a 96-well black microtiter plate (Greiner Japan Co.). A mixture of luminol (60 μL, 1 mmol/L), OZ (25 μL, 10 mg/mL) and HEPES-buffered saline (65 μL, pH 7.4) was simultaneously added into each well of the black microtiter plate using an automatic dispenser in a parallel luminometer (Alpha-Basic 47, Tokken Inc.).…”
Section: Measurement Of Serum Opsonic Activitymentioning
confidence: 99%
“…[3] In a summer training camp, strenuous physical exercises are carried out to improve endurance ability. [4][5][6] Training fatigue is the normal result of several days of heavy training associated with an overload training stimulus. [3] Stress is defined as a state of disharmony provoked by a psychological, environmental or physiologic stressor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation